Between ‘Labour Migration’ and ‘New European Mobilities’: Motivations for Migration of Southern and Eastern Europeans in the EU - Fischer-Souan, Maricia (Social Inclusion, 2019)
This article investigates in comparative perspective different accounts of the motivations for migration offered by Bulgarian, Romanian, Italian and Spanish nationals living in another EU country, or planning to move. In-depth interviews yield a range of accounts for the decision to leave the home-country, from narrowly defined economic motivations, professional and ‘qualitative’ labour market considerations, to desires for cultural/lifestyle exploration. Both individual and country-level factors are mobilised in motivational accounts, which are also set against the backdrop of major external shocks, such as the 2007 enlargement of the European Union and the 2008 global financial crisis. Findings highlight the need to consider the interplay between macro and individual-level factors—that is, perceptions of cultural, economic, political and societal structures as well as individual characteristics—in studying migratory behaviour. Moreover, the findings to a certain extent support the distinction between the ‘classic’ labour migration behaviour of Bulgarian and Romanian respondents and the ‘new European mobilities’ of Italian and Spanish participants, who emphasise more the overlapping professional, affective, cultural and quality of life considerations that shape the decision to move. However, convergence across groups may be expected in the future as East-West movers become more socialised into ‘new’ cultures of European mobility and as South-North migration patterns increasingly reinforce some of the ‘periphery-core’ dynamics of contemporary intra-EU mobility.